Surprising morphological diversity in ceraphronid wasps revealed by a distinctive new species of Aphanogmus (Hymenoptera: Ceraphronoidea) - Moser, Marina; Ulmer, Jonah M.; van de Kamp, Thomas; Vasilița, Cristina; Renninger, Maura; Mikó, István; Krogmann, Lars (European Journal of Taxonomy, 2023)
Within the well-studied Palearctic entomofauna, it is often assumed that the discovery of new species is limited to resolving cryptic species complexes within dark taxa. Herein, we describe a highly distinctive species of Aphanogmus Thomson, 1858 (Hymenoptera: Ceraphronidae) from Germany and provide a COI barcoding sequence for the new species. We present a 3D reconstruction of the holotype based on micro-CT to serve as a cybertype. The females of Aphanogmus kretschmanni Moser sp. nov. are diagnosed by two rows of prominent spines on the ventral edge of the 7th metasomal sternite, a character set that has not previously been found in Hymenoptera. We analyse the functional morphology of the ovipositor mechanism and discuss hypotheses regarding the functional implications of the unique modification of the 7th metasomal sternite. Possible host associations are reviewed and the taxonomic placement of the new species is discussed.